Optimización de la calidad del producto mediante la mejora del proceso de envasado en una empresa de leche envasada - Tejada Caceres, Jorge (2025)
This study aims to enhance product quality from a production perspective, due to the detection of bisphenol A (BPA), a compound that directly impacts final consumers. In response to this issue, a modification was implemented in the production process to eliminate BPA. Potential suppliers for a new varnish were considered, and three of them offered BPA-free options. A control sample was compared with these options over eight months, corresponding to the shelf life of canned milk at the point of sale. Ultimately, the supplier that offered the varnish with the least variation and preserved the product’s properties was chosen. The results were validated using relevant statistical tests based on data normality. In conclusion, evaluating the parameters related to product quality made it possible to identify the ideal supplier to replace the varnish in the production chain without affecting parameters that the consumer could detect.